Effect of different bicycle body positions on power output in aerobically trained females - Hubenig, L. R.; Game, A. B.; Kennedy, M. D. (Research in Sports Medicine, 2011)
Aerodynamic bicycle positioning reduces drag but also reduces power output (PO) in males. The effect of aerodynamic bicycle positioning in trained endurance females is unknown. Eighteen females participants (VO2max 49.7 ± 6.3 ml·kg-1·min-1) all with competitive experience performed cycling trials at ventilatory threshold 1 and 2 (VT-1, VT-2) in both an aerodynamic and an upright position. There was a significant difference in PO between the aerodynamic and upright positions at VT-1 (152.7 ± 28.0 Watts and 159.7 ± 33.1 Watts, respectively) but not at VT-2 (191.2 ± 39.1 Watts and 192.4 ± 40.0 Watts, respectively). There were no significant differences in heart rate, oxygen consumption, or cadence between positions at either intensity. At both intensities the individual response was varied and no trends due to years of experience or background (triathlete or cyclist) explained this variability. Therefore, despite the significant mean difference in PO at VT-1, these results indicate that in trained females the effect of aerodynamic positioning is individual.